(untitled) (The Journal of Plant Protection Sciences, 2022)
Soybean cyst nematode (Heterodera glycines, mixtures that are part of biological research on SCN) is the most destructive pathogen of varied fronts, from evolutionary investigations soybean (Glycine max (L.) Merr.), and is to cancer research. Recent advances in mass responsible for estimated annual yield losses of spectrometry, the establishment of various 457 to 819 million (2003-2005) in the United protein databases, and availability of high